Iron and the Breastfed Infant - James Friel; Wafaa Qasem; Chenxi Cai (MDPI AG, 2018)
The first 6 months of life is a crucial time in meeting iron needs. The purpose of this review is to examine iron in mother's milk and whether or not it meets the physiological needs of the growing infant. Key issues include iron content and iron transport from the mammary gland as well as when and what foods should be added to the solely breastfed infant. We examine these topics in light of new molecular biology findings in the mammary gland.